CAD/CAM learning processes: from geometric iterations to prototypes - Véliz Fadic, Felipe (Universidad de Lima. Carrera de Arquitectura, 2020)
Using digital means in different activities —art, design, architecture, urban planning, among others—and on various scales has prompted the evolution and further execution of creative processes, by taking into advantage its capacity for representation, analysis and development. Thus, teaching CAD/CAM work methodologies has gained importance in university curricula in order to train students to employ tools in a reflective manner. This paper shows the methods used in a digital fabrication course, as well as its outcomes, and relates the stages of analogical and digital design to the materials’ characteristics and the production of objects and systems in a digital fabrication laboratory.